Seismic responses and design recommendations for a plate-shell integrated concrete liquid-storage structure. (August 2021) - Cheng, Xuansheng; Qi, Lei; Jing, Wei; Zhang, Shanglong
Abstract: The seismic capacity of a plate-shell integrated concrete liquid-storage structure (PSICLSS, a new type water treatment structure) is studied under different liquid storage conditions to obtain the most unfavorable liquid storage conditions and provide theoretical guidance for PSICLSS design and construction. In this paper, different liquid storage conditions are analyzed for the maximum displacements, principal stresses, hydraulic pressures and sloshing wave heights of liquids in the structure. The results show that different liquid storage conditions cause significant changes in PSICLSS responses. The principal stress caused by external liquid is larger than that caused by internal liquid and is maximum when both internal and external liquids are stored, close to the tensile strength of concrete. Different liquid storage conditions do not cause significant response changes in the hydraulic pressure and sloshing wave height of the liquid. The hydraulic pressure caused by internal water is higher than that caused by external liquid, but the sloshing wave height of external liquid is higher than that of internal liquid. Further, the structural and hydrodynamic response mechanisms caused by different peak accelerations are similar and only cause peak values to change significantly. Finally, some design and construction recommendations are proposed and applied to an actual project.